Perceived Risks and Effects of Heat Stress to Students and their Coping Strategies - PEÑAFLOR, BONDEE; CAMBRI, BEVERLY GAY (International Journal of Arts, Sciences and Education, 2025)
The study assessed the perceived risks and effects of heat stress to students and their coping strategies which could serve as input for policy and institutional innovation in the school. A cross-sectional survey research design was employed in this study covering 583 respondents. Data were analyzed using both descriptive and inferential statistics. Results show that the perceived risk with the highest weighted mean include: Hot weather during these days can cause sickness; People exposed to heat have a greater risk of developing serious diseases; and Heat is a potentially lethal risk. Meanwhile, the perceived effects of heat stress are: Tiredness/Exhaustion, difficulty in getting sleep, and not able to study well at home and in school. To address these effects, foremost of the students’ coping strategies is by drinking cold water, juice or carbonated drinks, followed by keeping a personal tumbler to keep drinking water. In addition, students wear comfortable clothes to enhance thermal comfort and bathe more frequently to cope with heat stress. They also utilized trees and parks as the preferred places to stay or resting space for thermal comfort during hot days. To address these, the school management employs initiatives such as conserving/maintaining greeneries and blue spaces, water dispenser made available at no cost to the students, adjustment in class schedules, installation of air conditioning units and/or provision of additional fans, and adopting flexible learning modalities. The students were satisfied with these initiatives of the school. Finally, there is significant relationship between the perceived risks with that of the perceived effects, the coping strategies, and the school’s interventions relative to heat stress. As students exhibit coping strategies, they are, in a way, reducing their risks. On the same manner, as the school management provides necessary interventions that address heat stress, the school also aid in lowering the risks and in enhancing the coping strategies of the students.